Mortalidade e efeitos subletais de Bacillus thuringiensis Berliner em Spodoptera albula (Walker, 1857) - Gonçalves, Kelly Cristina [UNESP] (2015)
Spodoptera albula is a polyphagous and cosmopolitan pest and in Brazil there are no products registered for their control although some farmers have recently been reported outbreaks of this specie in soybean in the Mato Grosso state. Thus, it is extremely important to developing effective tactics to control this pest that are less harmful to the environment and society. Bacillus thuringiensis (Bt) is a highly efficient entomopathogenic bacterium in lepidopterous pest control and it is toxic to several species of Spodoptera genus. The toxic activity of Bt isolates and Bt biopesticides was evaluated using S. albula second instar larvae in mortality and virulence bioassays, and evaluating the sublethal Bt effects on larvae surviving to treatment. The biopesticides Agree, Xentari and Dipel SC were selected for bioassay virulence. Agree was the most virulent and therefore the most promising for the S. albula management. It was also observed differences in toxicity between Dipel formulations. All Bt isolates tested were not good for the control of this pest and the isolate BT05 affected the development of larvae resulting in lower weight of pre-pupa and pupa compared to control